EMPOWERMENT OF THE JOGO TONGGO GROUP IN IMPROVING TRACKING CAPABILITIES AND INDEPENDENT ISOLATION IN MANGGIHAN VILLAGE, GETASAN DISTRICT, SEMARANG REGENCY - Wahyu Endang Setyowati; Nunik Nurhidayanti; Agustin Handayani (Caring : Jurnal Pengabdian Masyarakat, 2022)
Manggihan village, Getasan sub-district, Semarang district, Central Java province, which is one of the areas in Central Java, especially in Semarang district, is an area that is in the red zone related to the spread of Covid-19 in Indonesia. The existence of the Jogo Tonggo group, which is the mainstay project of the Central Java provincial government, needs to get support from all components of society. This fact encourages the importance of empowering the community to be able to independently help themselves in relation to prevention and handling of the increasingly endemic cases of Covid-19 transmission. Capacity building is an important thing that drives the success of the Movement to break the chain of transmission of Covid-19 through tracking or self-isolation management. The purpose of this activity is to improve the ability of tracking and independent isolation in Manggihan Village, Getasan District, Semarang Regency through the empowerment of the Jogo Tonggo group. The method of implementing activities is a group-based method that is carried out comprehensively which is able to take an inventory of all aspects of HR or human resources through IEC, namely Communication, Information and Education.